Predictors of surgery choices in women with early-stage breast cancer in China: a retrospective study - Sijia Huang; Qingmo Yang; Xujuan Zheng; Ka Ming Chow; Junhua Wu; Jiemin Zhu (BMC Cancer, 2023)
Abstract Background The breast-conserving surgery and reconstruction rate in China is relatively low when compared with those in Western countries. Moreover, predictors of surgical choices for women with breast cancer in China have not yet been explored. This study aims to explore differences in the surgical choices of women with different demographic and clinical characteristics and the predictors that influence surgical choices of women with early-stage breast cancer. Methods This retrospective study included women with early-stage (0-II) breast cancer who underwent surgeries at one of two Xiamen University-affiliated hospitals between 2009 and 2017. Using medical records, eleven variables were collected: the woman's age, year of diagnosis, hospital, marital status, payment method, cancer stage, presence of positive axillary lymph node, histology, neoadjuvant chemotherapy, radiotherapy, and the type(s) of surgery they chose. Binary logistic regression was used to analyse predictors of surgical choice. Results A total of 1,787 cases were included in this study. Of the total number of women with breast cancer, 61.3% underwent mastectomy without breast reconstruction, 26.4% underwent mastectomy with breast reconstruction, and the remaining 12.2% chose breast-conserving surgery. Women with different demographic and clinical characteristics underwent different types of surgery. Cancer stage, neoadjuvant chemotherapy, radiotherapy, and the choice of hospital were found to be predictors of breast-conserving surgery. Meanwhile, age, year of diagnosis, payment method, neoadjuvant chemotherapy, and the choice of hospital were found to be predictors of reconstruction after mastectomy in women with early-stage breast cancer. Conclusions In China, surgical choices for women with breast cancer have diversified. Healthcare workers should understand the surgical preferences of women of different ages. For early detection of breast cancer, knowledge of breast self-examination and breast cancer screening should be provided. Adequate information about the safety of reconstruction and advocacy for medical insurance coverage of reconstruction should be offer. Breast surgeons need specialised training and standardising protocols towards different types of breast surgery. These actions will help women make better, well-informed decisions about their breast surgeries.